The Institutional Behavior of the Royal House on Instagram: A Relational Perspective - Pulido-Polo, Marta; Mesa-Göbel, José Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2026)
2024 is a key year for Casa Real because it involves the reinforcement of relational strategies aimed at the positioning of the Heir, the legitimization of the Royal Family and the public approach to citizens. The objective is to identify the keys that mark the relational behavior of the Royal House on Instagram, observing the role played by protocol and the organization of events. A multivariate quantitative study is carried out with SPSS (Krippendorff's alpha coefficient = 0,89) on the corpus made up of all publications made between June 24, 2024 and January 24, 2025.